2009
DOI: 10.1091/mbc.e08-10-1051
|View full text |Cite
|
Sign up to set email alerts
|

XMAP215–EB1 Interaction Is Required for Proper Spindle Assembly and Chromosome Segregation in Xenopus Egg Extract

Abstract: In metaphase Xenopus egg extracts, global microtubule growth is mainly promoted by two unrelated microtubule stabilizers, end-binding protein 1 (EB1) and XMAP215. Here, we explore their role and potential redundancy in the regulation of spindle assembly and function. We find that at physiological expression levels, both proteins are required for proper spindle architecture: Spindles assembled in the absence of EB1 or at decreased XMAP215 levels are short and frequently multipolar. Moreover, the reduced density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 62 publications
4
28
0
Order By: Relevance
“…The concentration of EB1 in vertebrate cytoplasm has previously been reported as ranging between 0.25 and 2 µM in Xenopus egg extract [Tirnauer et al, 2002; Kronja et al, 2009] and tens of nanomolar in S. pombe [Katsuki et al, 2009]. We estimated the concentration of EB1 in HeLa cells to be ~0.25 µM using quantitative western blots (Table I and Supporting Information Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of EB1 in vertebrate cytoplasm has previously been reported as ranging between 0.25 and 2 µM in Xenopus egg extract [Tirnauer et al, 2002; Kronja et al, 2009] and tens of nanomolar in S. pombe [Katsuki et al, 2009]. We estimated the concentration of EB1 in HeLa cells to be ~0.25 µM using quantitative western blots (Table I and Supporting Information Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Differences or changes in the dimerization properties of the three EBs may, therefore, contribute to the differences in the anti-catastrophe activity. Interestingly, C-terminal EB dimerization domains act as dominant negative mutants and have been used in an array of cellular studies as tools to interfere with the activity of endogenous EB proteins (9,20,(25)(26)(27)(28)(29)(30)(31)(32). They were found to affect all EB species by removing them from microtubule plus ends, which results in an increase in the catastrophe frequency (9).…”
mentioning
confidence: 99%
“…Transient overexpression of EB1 or EB3 C-terminal domains has been used as a tool in many studies with the intent to interfere with the binding of ϩTIPs with endogenous full-length EBs in different cell types (9,20,(25)(26)(27)(28)(29)(30)(31)(32). We recently showed that a very similar dominant negative effect is also obtained with an EB1 C-terminal domain lacking the tail region, which is essential for partner binding (9), indicating that sequestration of ϩTIP binding partners is not the prevailing mode of interference.…”
mentioning
confidence: 99%
“…In Xenopus egg extracts, an interaction between EB1 and XMAP215 is important for physiological MT growth rates between 10 and 20 m/min, proper spindle assembly, and chromosome segregation (58). This effect was investigated in vitro, where EB1 and XMAP215 combined had a much larger effect on MT growth rates than XMAP215 (10-fold increase) or EB1 (1.5-fold increase) alone with rates up to 20 m/min, the highest rates ever observed outside cells (Fig.…”
Section: Adding Complexity Via ؉ Tipsmentioning
confidence: 99%